Solve the Hanoi Puzzle Using Difference Equations - Hamza M. Salman; Huda Amer Hadi (Scientific Trends, 2022)
This research aims to solve an old riddle invented by the French mathematician (Edward Lucas) in the year 1883 AD, known as ( Tower of Hanoi puzzle) using difference equations, which we will address in terms of its concept, some characteristics, types, methods of solving each type of them and some illustrative examples.
Keywords: Difference Equations. Homogenous first order Linear Difference Equations.Higher order Linear Difference with constant coefficients.